Irreducible Generic Gelfand-Tsetlin Modules of gl(n) - Futorny, V.; Grantcharov, D.; Ramirez, L.E. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
We provide a classification and explicit bases of tableaux of all irreducible generic Gelfand-Tsetlin modules for the Lie algebra gl(n).